Bejijong Community's Perception of Village Service E-government as a Self-Service System - Fadhilah, Laila Nur; Rochmaniah, Ainur (Procedia of Social Sciences and Humanities, 2024)
Bejijong Village has the goal of creating digital-based public services. This is a factor in the creation of a self-service system. The purpose of this study is to analyze the perception of the Bejijong community towards E-government Village Services as a Self-Service System. This study uses a qualitative method to interpret an understanding related to the cause and effect of a phenomenon and uses a descriptive type in order to systematically describe the community's perception of Village Services as a self-service in Bejijong village. This research was conducted in Bejijong Village, Trowulan District, East Java. In this study, purposive techniques are used to determine informants. The data collection techniques used are interviews and observations. Primary data was obtained by conducting direct interviews with 5 informants who are people of Bejijong Village, both who use self-service and non-self-service, while secondary data is obtained from previous researches and internet media such as google and e-book. The data analysis in this study uses Miles and Huberman interactive analysis, namely data collection, data presentation and conclusion drawn. This study uses Stephen P. Robbins' theory of perception which consists of 2 indicators, namely acceptance and evaluation. The results of the study show that all indicators get a positive or good perception from the public. Because the self-service system provides convenience for them in taking care of correspondence that requires information from the village. Of the 5 informants that have been interviewed by the researcher, there is 1 informant who stated that he could not use self-service, this is due to the age factor and lack of understanding of information technology.